Spontaneous lower lip abscess in an immunocompetent individual - Prawash Sunuwar; Lakshmi Venkatakrishnan; Thomas Aldridge (Advances in Oral and Maxillofacial Surgery, 2025)
An abscess is a localized collection of pus within tissue, often due to a bacterial infection. Lip abscesses are particularly rare, especially in immunocompetent individuals, as the lip is typically protected by keratinized mucosa and a good blood supply and lacks common sources of infection. Common causes of lip swelling include allergic reactions, trauma, and specific vascular or lymphatic malformations, such as haemangiomas and lymphangiomas. This article presents a rare case of a spontaneous lower lip abscess in an immunocompetent individual, discussing the clinical approach, surgical management, and a review of literature for insights into diagnostic and treatment challenges.